Challenged for Higher-Order Thinking Skill Implementation: Reports From EFL Classroom Teachers (International Journal of Language Teaching and Education, 2019)
Higher-Order Thinking Skills (HOTS) become the current educational issues in Indonesia. The teachers have to be aware of its importance and have sufficient knowledge about it. This study aims to investigate junior high school teachers’ perceptions and challenges in employing HOTS in the EFL classroom. This case study involved two junior high school English teachers from different schools. Data were collected through interviews and classroom observation for triangulation purposes. The findings showed that teachers have been conscious of the importance of HOTS, but they have different perceptions and different ways of implementing HOTS in their EFL classroom. However, there are also challenges that the teachers have to face when they employ HOTS in their classrooms.